TAAR9 knockout increases hippocampal serotonin and alters grooming behavior in rats - Zhukov, Ilya S.; Karpova, Inessa V.; Murtazina, Ramilya Z.; Alnefeesi, Yazen; Korenkova, Olga M.; Tissen, Ilia Yu.; Palchikova, Svetlana A.; Tokareva, Lydia A.; Pyurveev, Sarng S.; Shabanov, Petr D.; Kubarskaya, Larisa G.; Rozhko, Mikhail A.; et al. (Frontiers in Pharmacology, 2025)
IntroductionDespite their association with brain disorders, the neurophysiological roles of the trace amine-associated receptors remain poorly understood. In humans, the genomic trace amine-associated receptor cluster comprises nine consecutive genes, six of which code for functional proteins (TAAR1, TAAR2, TAAR5, TAAR6, TAAR8, TAAR9). While homologues of the former three are known to regulate classical monoamines and neurogenesis, the functions of the latter three remain largely unknown. In this exploratory study, we demonstrate for the first time that TAAR9 plays a significant regulatory role in the monoaminergic systems of the rat.MethodsWe used qPCR to measure TAAR9 mRNA expression throughout the rat brain. Serotonin, dopamine, and their metabolite levels were assessed by HPLC in brain tissues from TAAR9-KO and wild-type littermates. We applied fast-scan cyclic voltammetry to measure mesolimbic dopamine release. Behavioral analysis included assessment of grooming, anxiety-like, and sexual behaviors. A battery of hematological/hormone assays was also applied.Results and discussionWe detected TAAR9 mRNA in the brainstem and midbrain–regions that include key monoaminergic nuclei such as the locus coeruleus, raphe nuclei, and the ventral tegmental area. The TAAR9-KO rats exhibited increased hippocampal serotonin levels and a slight shift in dopamine turnover, but not mesolimbic dopamine release. Although hippocampal serotonin is commonly implicated in mood and anxiety regulation, behaviorally, no genotype differences were detected in the elevated plus maze, suggesting that basal anxiety-like behavior remained unaffected under the test conditions. However, changes in grooming microstructure indicated subtle alterations in behavioral organization, which may reflect the neurochemical changes observed in the hippocampus. No changes were evident in a battery of hematological assays.ConclusionTogether, these findings suggest that TAAR9 deletion selectively modulates central monoaminergic systems and related behavioral patterns, without altering systemic physiological parameters.